Gain‐of‐function STAT1 mutations impair STAT3 activity in patients with chronic mucocutaneous candidiasis (CMC). Issue 10 (1st September 2015) - Zheng, Jie; van de Veerdonk, Frank L.; Crossland, Katherine L.; Smeekens, Sanne P.; Chan, Chun M.; Al Shehri, Tariq; Abinun, Mario; Gennery, Andrew R.; Mann, Jelena; Lendrem, Dennis W.; Netea, Mihai G.; Rowan, Andrew D.; et al.
<x xml:space="preserve">Abstract</x> Signal transducer and activator of transcription 3 (STAT3) triggered production of Th‐17 cytokines mediates protective immunity against fungi. Mutations affecting the STAT3/interleukin 17 (IL‐17) pathway cause selective susceptibility to fungal (Candida) infections, a hallmark of chronic mucocutaneous candidiasis (CMC). In patients with autosomal dominant CMC, we and others previously reported defective Th17 responses and underlying gain‐of‐function (GOF) STAT1 mutations, but how this affects STAT3 function leading to decreased IL‐17 is unclear. We also assessed how GOF‐STAT1 mutations affect STAT3 activation, DNA binding, gene expression, cytokine production, and epigenetic modifications. We excluded impaired STAT3 phosphorylation, nuclear translocation, and sequestration of STAT3 into STAT1/STAT3 heterodimers and confirm significantly reduced transcription of STAT3‐inducible genes (RORC/IL‐17/IL‐22/IL‐10/c‐Fos/SOCS3/c‐Myc) as likely underlying mechanism. STAT binding to the high affinity sis‐inducible element was intact but binding to an endogenous STAT3 DNA target was impaired. Reduced STAT3‐dependent gene transcription was reversed by inhibiting STAT1 activation with fludarabine or enhancing histone, but not STAT1 or STAT3 acetylation with histone deacetylase (HDAC) inhibitors trichostatin A or ITF2357. Silencing HDAC1, HDAC2, and HDAC3 indicated a role for HDAC1 and 2. Reduced STAT3‐dependent gene transcription underlies low Th‐17 responses in GOF‐STAT1 CMC, which can be reversed by inhibiting acetylation, offering novel targets for future therapies.